As (III) and Cd (II) ion imprinting electrochemical sensor and electrochemical detection method

By developing a dual-template ion-imprinted electrochemical sensor based on amino-functionalized zirconium-based metal-organic framework composite bismuth nanoparticles, the problem of simultaneous high-sensitivity detection of arsenic and cadmium ions in water in existing technologies has been solved, achieving low-cost, rapid, and accurate multi-target detection.

CN120870265APending Publication Date: 2025-10-31YUNNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510963688.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing technologies cannot simultaneously detect arsenic (As(III)) and cadmium (Cd(II)) ions in water with high sensitivity without causing interference. Furthermore, traditional methods are costly or prone to inactivation, making it difficult to achieve rapid detection of multiple targets.

Method used

A dual-template ion-imprinted electrochemical sensor based on amino-functionalized zirconium-based metal-organic framework composite bismuth nanoparticles was developed. The sensor is constructed using a three-layer composite sensing membrane, comprising amino-functionalized zirconium-based metal-organic framework material, bismuth nanoparticles, and an ion-imprinted polymer membrane, and is detected by differential pulse anodic stripping voltammetry.

Benefits of technology

It enables simultaneous detection of As(III) and Cd(II), exhibiting high sensitivity, good selectivity, and anti-interference performance, with a detection limit as low as 1.3×10-10 mol·L-1, making it suitable for water pollution monitoring and drinking water safety assessment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120870265A_ABST
    Figure CN120870265A_ABST
Patent Text Reader

Abstract

The invention discloses an As (III) and Cd (II) ion imprinting electrochemical sensor and an electrochemical detection method. The sensor takes a glassy carbon electrode as a substrate, an amino-functionalized zirconium-based metal organic framework material is modified by a dispensing method, and then bismuth nanoparticles are deposited on the surface of the amino-functionalized zirconium-based metal organic framework material to form a composite interface. Then, an As (III)-Cd (II) double-template ion imprinted polymer membrane based on the simulated and optimized functional monomer proportion is constructed on the composite interface, and AsCd-IIM / NH2-UiO-66 (Zr) (at) Bi / GCE is obtained. The sensor shows a good linear relationship in a concentration range of 0.0002 to 32.3 [mu] mol. L <-1 >. The detection limit is as low as 1.3 * 10 <-10 > mol.L <-1 > (S / N = 3). Compared with a traditional detection method and a non-imprinted control group, the sensor and the detection method developed by the invention show higher sensitivity and anti-interference capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical sensing technology, and in particular to an As(Ⅲ) and Cd(Ⅱ) dual-ion imprinted electrochemical sensor based on the interface of amino-functionalized zirconium-based metal-organic framework composite bismuth nanoparticles (NH2-UiO-66(Zr)@Bi) and its electrochemical detection method. The sensor is used for the simultaneous and highly sensitive detection of As(Ⅲ) and Cd(Ⅱ) ions in environmental water. Background Technology

[0002] Arsenic (As(III)) and cadmium (Cd(II)) are typical heavy metal pollutants that often coexist in water bodies polluted by metallurgy, mining, electronics manufacturing, and agricultural irrigation runoff, posing a significant risk of synergistic pollution. As(III) is highly carcinogenic and neurotoxic; long-term exposure can induce skin lesions, respiratory diseases, and even bladder cancer. Cd(II), on the other hand, easily accumulates in the human body, affecting kidney function and bone metabolism, and can cause chronic toxicity through food chain migration. Furthermore, the synergistic presence of As(III) and Cd(II) has a potential stress effect on aquatic ecosystems, affecting phytoplankton community structure and reducing the self-purification capacity of water bodies. Studies have also shown that the two may exhibit competitive or synergistic adsorption behaviors in coexisting states, altering their environmental mobility and toxicity release patterns. To control the harm and risks posed by these substances, the World Health Organization (WHO) and the U.S. Environmental Protection Agency (EPA) have set the recommended safety limit for arsenic in drinking water at 10 µg / L, and the recommended safety limit and maximum contaminant level (MCL) for cadmium at 3 µg / L and 5 µg / L, respectively. Therefore, ensuring the simultaneous identification and joint monitoring of As(III) and Cd(II) heavy metals in water bodies is of great significance for maintaining the safety standards and ecological health of natural water bodies.

[0003] Given the persistent and bioaccumulative toxicity of As(III) and Cd(II), posing threats to human health and the environment, stringent regulations and standards have been established globally to control heavy metal content in drinking water. Effective detection and monitoring are the first line of defense against heavy metal pollution. Currently, commonly used methods for determining As(III) and Cd(II) content in water include inductively coupled plasma mass spectrometry (ICP-MS), atomic absorption spectrometry (AAS), inductively coupled plasma optical emission spectrometry (ICP-OES), electrochemical methods, colorimetric methods, and reagent kit methods. ICP-MS is currently the most accurate and precise method for detecting arsenic and cadmium content in water, but the equipment is expensive and requires specialized laboratories and technicians. Colorimetric and reagent kit methods, while simple to operate, are susceptible to interference and have low selectivity, and are often used for initial screening. Electrochemical analysis techniques, due to their high sensitivity, accuracy, and wide linear dynamic range, are considered one of the most accurate and timely analytical methods in the field of heavy metal analysis. Increasingly, heavy metal analysis is relying on electrochemical analysis to detect them without traditional methods. However, as research progresses, the application of pure electrodes to detect As(III) and Cd(II) in the same solution often encounters several problems: when arsenic and cadmium coexist, they exhibit different electrochemical behaviors, mainly manifested in competitive adsorption or mutual interference or even suppression of each other's signals due to changes in the local chemical environment. This makes it difficult to find a suitable potential range for detecting both without interference. Furthermore, achieving simultaneous and rapid detection of multiple targets using sensors is a significant challenge, requiring sensors to not only have sensitive responses to multiple targets but also possess good selectivity and anti-interference capabilities. Most sensors with anti-interference selectivity are based on biorecognition elements (e.g., antigen / antibody-based sensors, DNA-based sensors, and aptamer sensors), which are expensive and prone to deactivation. This severely hinders the development of rapid AsCd analysis in environmental analysis and identification. Summary of the Invention

[0004] This invention addresses the shortcomings of existing technologies by, for the first time, attempting and developing a dual-template imprinted electrochemical sensor with an ultra-low detection limit that can simultaneously detect As(III) and Cd(II) ions in liquids. Furthermore, its electrochemical detection method has been optimized and developed.

[0005] This invention discloses an As(III) and Cd(II) ion-imprinted electrochemical sensor, comprising a substrate electrode and a surface ion-imprinted composite sensing film coated on the surface of the substrate electrode; the composite sensing film consists of three layers from bottom to top, comprising:

[0006] (1) Amino-functionalized zirconium-based metal-organic framework material NH2-UiO-66(Zr) layer;

[0007] (2) Bismuth nanoparticles (Bi-NPs) layer attached to the amino-functionalized zirconium-based metal-organic framework material NH2-UiO-66(Zr) layer;

[0008] (3) As(Ⅲ) and Cd(Ⅱ) ion-imprinted polymer film (AsCd-IIM) formed by infrared-initiated polymerization.

[0009] The substrate electrode is selected from one of glassy carbon electrode, screen-printed electrode, and carbon paste electrode.

[0010] Preferably, the substrate electrode is a glassy carbon electrode (GCE) that has undergone pretreatment; the diameter is 3 to 6 mm.

[0011] The pretreatment process includes: polishing the glassy carbon electrode sequentially with alumina powder with particle sizes of 0.5 μm, 0.3 μm, and 0.05 μm; then ultrasonically cleaning it sequentially with pure water, ethanol, and pure water for 2–5 min, followed by air drying; then placing the electrode in a sulfuric acid solution with a concentration range of 0.1–1.0 mol / L, and performing 5–20 cyclic voltammetric scans at -0.3–1.3 V with a scan rate of 20–100 mV / s under stirring conditions to activate the electrode; then performing cyclic voltammetric scans in a buffer solution containing 0.1 mol / L potassium chloride and 5 mmol / L K3[Fe(CN)6] / K4[Fe(CN)6] (pH 6.0) until a stable cyclic voltammogram is observed, followed by washing with ultrapure water. The electrode is then air-dried for later use.

[0012] Preferably, an amino-functionalized zirconium-based metal-organic framework material NH2-UiO-66(Zr) layer is disposed on the pretreated glassy carbon electrode, including the following schemes:

[0013] Dissolve 0.1–1.0 mmol of ZrCl4 and 0.1–1.0 mmol of NH2-BDC (phthalic acid) in 10–30 mL of DMF; after mixing thoroughly, add 0.5–3.0 mL of acetic acid and sonicate for 10–20 minutes; then transfer the mixture to a 50–100 mL, preferably 50 mL, high-pressure reactor and react at 115–125 °C, preferably 120 °C, for 12–24 h; after cooling, wash at least twice with DMF to remove unreacted raw materials and impurities, then wash with ethanol, and finally centrifuge to collect the centrifuged product. The centrifuged product is then vacuum dried at 115–125 °C for 20–28 h to obtain NH2-UiO-66 (Zr). In practical applications, after cooling to room temperature, the product can be washed three times with DMF to remove unreacted raw materials and impurities, then further washed with ethanol to improve purity, and finally centrifuged to collect the product and dried under vacuum for 24 hours (120℃) to obtain NH2-UiO-66(Zr).

[0014] 0.5–5.0 mg of NH2-UiO-66(Zr) prepared by the above method was dispersed in 1.0–5.0 mL of ethanol and sonicated for 8–15 min to obtain a uniform and stable suspension. Subsequently, 2–5.0 μL of the suspension was dropped onto the surface of the pretreated glassy carbon electrode in two separate drops to obtain NH2-UiO-66(Zr) / GCE.

[0015] Preferably, a layer of bismuth nanoparticles (Bi-NPs) is arranged on NH2-UiO-66(Zr) / GCE, including the following schemes:

[0016] Immerse NH2-UiO-66(Zr) / GCE in a solution containing 0.1 ~ 1.0 mM Bi 3+ In a PBS electrolyte solution, under stirring conditions, uniform sodium bismuth nanoparticles were deposited at a constant potential of -0.9 to -1.2 V for 70 to 300 s using a potentiostatic method. These particles were then gently washed with pure water and dried to obtain an NH₂-UiO-66(Zr)@Bi / GCE modified electrode. The PBS electrolyte solution was 0.1 to 0.5 M. In practical applications, Bi... 3+ It can be provided by bismuth nitrate, the drying includes natural air drying, and the stirring includes electromagnetic stirring.

[0017] Preferably, the As(III) and Cd(II) ion-imprinted polymer films formed by infrared-initiated polymerization on the NH2-UiO-66(Zr)@Bi / GCE modified electrode include the following schemes:

[0018] The template-functional monomer polymerization solution was dissolved in 300-500 μL of acetonitrile. Then, 10.0-50.0 μL of the polymerization solution was added dropwise to the surface of the NH2-UiO-66(Zr)@Bi / GCE modified electrode. After covering with a glass slide, the polymerization was carried out under infrared lamp irradiation for 2-6 hours. Then, the template ions As(Ⅲ) and Cd(Ⅱ) were removed by elution solution to obtain AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE.

[0019] As(III) and Cd(II) ion-imprinted polymer films are formed by infrared-initiated polymerization, with the wavelength of the red light used being 700~1000 nm.

[0020] Preferably, the template-functional monomer polymerization solution is prepared through the following steps:

[0021] Sodium arsenite, cadmium acetate dihydrate, and functional monomers MAA and 4-(2-pyridinium azo)resorcinol (PAR) were dissolved in 300-800 μL of acetonitrile at a molar ratio of 1:1:1:1 to 1:2:4:4. After sonication for 8-15 min, the mixture was allowed to stand to allow the template and monomers to react fully. Then, 0.1-1.0 mmol of ethylene glycol dimethacrylate was added, and sonication was continued for 3-10 min. Afterward, 0.01-0.08 mmol of azobisisobutyronitrile was added, and the mixture was sonicated for 5-15 min before being stored in a refrigerator. Before adding NaAsO2 to acetonitrile, the prepared NaAsO2 was first dissolved in 50-100 μL of ultrapure water. After dissolving in acetonitrile, the concentration of sodium arsenite was 0.0125-0.05 mmol / L, preferably 0.025 mmol / L. To ensure that the template and monomers can fully interact, the settling time is generally greater than or equal to 6 hours. To improve efficiency, it is generally recommended to settling overnight.

[0022] Preferably, the eluent consists of 0.01-0.05 M EDTA (ethylenediaminetetraacetic acid) and 0.1-0.5 M HCl, with a volume ratio of 1-2:1-2. In industrial applications, soaking in a mixture of 0.05 M EDTA and 0.1 M HCl at a volume ratio of 1:1 for 10 minutes can achieve efficient removal of As and Cd.

[0023] As a preferred option, azobisisobutyronitrile is added, and after sonication, it is stored in a refrigerator at 2-8°C.

[0024] During the technology development process, the type and proportion of functional monomers in the template-functional monomer polymerization liquid were optimized by Gaussian 16W software based on density functional theory (DFT). The M06-2X functional and the def2SVP / LANL2DZ mixed basis set were selected. The optimal combination of functional monomers and their molar ratio were screened out through binding energy calculation and experimental exploration and analysis.

[0025] During the technological exploration process, a control sensor (NIM / NH2-UiO-66(Zr)@Bi / GCE) without imprinting membrane modification was prepared under the same conditions without adding As(Ⅲ) and Cd(Ⅱ) template ions.

[0026] This invention discloses an electrochemical detection method for an As(III) and Cd(II) ion-imprinted electrochemical sensor. Using the As(III) and Cd(II) ion-imprinted electrochemical sensor as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum column electrode as the counter electrode, differential pulse anodic stripping voltammetry (DPASV) is used to measure buffer solutions B with different As(III) and Cd(II) concentrations. Differential pulse curves of As(III) and Cd(II) are plotted, and standard curves of As(III) and Cd(II) are obtained by plotting the relationship between peak current and As(III) and Cd(II) concentrations. The As(III) and Cd(II) ion-imprinted electrochemical sensor is an AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE modified electrode.

[0027] Preferably, buffer solution B is phosphate buffered saline (PBS) with a concentration of 0.1–0.5 mol / L, containing 0.1–0.5 mol / L KCl, and a pH of 5–10. The concentrations of As(III) and Cd(II) in buffer solution B are 1.0 × 10⁻⁶. -10 ~5.0 ×10 -5 mol / L.

[0028] The solution includes an aqueous solution.

[0029] Preferably, the DPASV voltammetric method has an initial potential of -1.2V, an end potential of 1.0V, a pulse amplitude of 0.01~0.05s, a pulse period of 0.1~0.5s, an amplitude of 0.01~0.05V, and an enrichment time of 50~300s.

[0030] This invention discloses an electrochemical detection method for an As(III) and Cd(II) ion-imprinted electrochemical sensor, wherein the concentrations of As(III) and Cd(II) in the detection solution are 2.0 × 10⁻⁶. -10 ~3.2 ×10 -5 At mol / L, the sensor exhibits good linear response to As(Ⅲ) and Cd(Ⅱ).

[0031] This invention discloses an electrochemical detection method for As(III) and Cd(II) ion-imprinted electrochemical sensors, with detection limits for As(III) and Cd(II) as low as 1.3 × 10⁻⁶. -10 mol·L -1 (S / N = 3) This device is used for the simultaneous detection of trace As(III) and Cd(II) heavy metal ions in environmental water samples. It has high sensitivity, good selectivity and anti-interference performance, and is suitable for water pollution monitoring, drinking water safety assessment and other scenarios.

[0032] Principles and advantages

[0033] The principle of simultaneous electrochemical detection of As(III) and Cd(II) heavy metal ions consists of two steps. The first step is pre-enrichment, which involves enriching As(III) and Cd(II) on a modified electrode at a potential of -1.2V in 10 mL of 0.1 M PBS (pH=6) electrolyte solution containing a certain concentration of As(III) and Cd(II) heavy metal ions. The reactions that occur in this process are as follows:

[0034] As 3+ +3e - As 0

[0035] Cd 2+ +2e - Cd 0

[0036] The second step is dissolution. After arsenic and cadmium ions are enriched on the working electrode, the potential is scanned at a constant rate using the DPV method (differential pulse voltammetry). The metal deposited on the modified electrode will then be oxidized under a specific voltage. The reactions that occur in this process are as follows:

[0037] As 0 -3e - As 3+

[0038] Cd 0 -2e - Cd 2+

[0039] The peak current is proportional to the measured ion. The current is measured and the corresponding potential is recorded to calculate the metal ion concentration.

[0040] This invention develops a novel dual-template sensor-imprinted electrochemical sensor (AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE) that enables simultaneous detection of As(III) and Cd(II), demonstrating the advantages of a multi-target detection strategy. The sensor is fabricated by modifying the surface of a glassy carbon electrode using a three-layer continuous film of NH2-UiO-66(Zr), Bi-NPs, and AsCd-IIM. The composite film increases the contact area with the analytes and improves the electrocatalytic behavior of the sensor for As(III) and Cd(II). Under optimized conditions, such as an AsCd template, MAA, PAR, and EGDMA in a ratio of 1:1:3:3:40, the imprinted sensing electrode prepared in this invention achieves a concentration range of 2.0 × 10⁻⁶ in water samples. -10 ~3.2 ×10 -5Within the range of mol / L, the sensor exhibits good linear response to As(III) and Cd(II). The detection limits for As(III) and Cd(II) in this invention can be as low as 1.3 × 10⁻⁶. -10 mol·L -1 (S / N = 3), the excellent robustness of AsCd and MAAPAR analysis is attributed to the ion trap formed by MAAPAR N6 / 13 and O21 / 22. Furthermore, the newly designed dual-template IIP sensor exhibits superior reproducibility, repeatability, stability, and high selectivity compared to NIP. This sensor can be used for the analysis of real samples and yields satisfactory results.

[0041] Compared with traditional detection methods and the unimprinted control group, the sensor and detection method developed in this invention exhibit higher sensitivity and anti-interference ability. Currently, there are no literature reports on the use of AsCd-IIM and NH2-UiO-66(Zr)@Bi composite materials for electrode modification in the simultaneous detection of As(III) and Cd(II), demonstrating significant technological advancement and application potential. Attached Figure Description

[0042] Figure 1 The images show the XRD patterns (a) and FTIR spectra (f) of NH2-UiO-66(Zr)@Bi (x1, F4), AsCd-IIM / NH2-UiO-66(Zr)@Bi before elution (x2, F1) and after elution (x3, F2), and NIM / NH2-UiO-66(Zr)@Bi (x4, F3) prepared in Example 1; the SEM images of NH2-UiO-66(Zr)(b), NH2-UiO-66(Zr)@Bi(c), and AsCd-IIM / NH2-UiO-66(Zr)@Bi before elution (d) and after elution (e); and the EDX spectra of AsCd-IIM / NH2-UiO-66(Zr)@Bi before elution (g) and after elution (h).

[0043] Figure 2 The following are optimized simulation diagrams showing the composite geometry and hydrogen bonds formed at different binding sites of the [As(Ⅲ)Cd(Ⅱ) + nMAAPAR] (1≤n≤4) complex in Example 1 with different molar ratios: a: 1:1:1:1; b: 1:2:2:2; c: 1:2:3:3; d: 1:2:4:4.

[0044] Figure 3For Example 2, in a 5.0 mM K3Fe(CN)6 / K4Fe(CN)6 (1:1) solution containing 0.1 M KCl, cyclic voltammetry (CV) plots (A) and electrochemical impedance spectroscopy (Nyquist plot B) of different modified electrodes are shown. (EIS frequency range: 100 kHz–0.1 Hz, amplitude: 0.01 V). (a) Bare GCE, (b) NH2-UiO-66(Zr)@Bi / GCE, (c) AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE, (d) IIM / NH2-UiO-66(Zr) / GCE after AsCd elution.

[0045] Figure 4 In Example 3, at 0.1 mol L -1 The linear relationship (B) between the peak DPV oxidation current (A) of AsCd-MIM / NH2-Zr-MOF@Bi / GCE on AsCd in PBS buffer solution (pH 6.0) and the logarithm of its concentration; with continuous addition of 1.0 × 10⁻⁶ -10 - 5.0×10 -5 mol L -1 Linear relationship between DPASV response current and the logarithm of concentration for Cd (C) and As (D); a: 0; b: 2.2 × 10⁻⁶ -10 c: 6.0×10 -10 ; d: 1.0×10 -9 e: 3.0×10 -9 f: 1.5×10 -8 g: 6.4×10 - 8 h: 2.9×10 -7 i: 1.2×10 -6 j: 5.9×10 -6 k: 3.2×10 -5

[0046] Figure 5 The AsCd-MIM / NH2-Zr-MOF@Bi / GCE and NIP sensors in Example 5 were used for 5.0 μmol L -1 AsCd, 15.0 μmol L -1 Peak current responses of Cu(II), Mg(II), Pd(II), Ca(II), K(I), Na(I), Cl(-I), SO4(-II), Vc and Glc (error bars indicate the standard deviation of the results when n=3). Detailed Implementation

[0047] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the content described.

[0048] Ion-imprinted nanofilms (IIMs) are prepared by using target ions as templates, immobilizing them through coordination crosslinking, and then extracting the target analyte from a supramolecular polymer containing the optimal absorption conformation of the target ion. The resulting membrane material exhibits high antigen / antibody-like recognition upon encountering the target ion, thus possessing high selectivity and anti-interference capabilities. Using IIM as a modifying material for electrochemical sensors, combined with the large specific surface area, tunable porosity, and unique electrocatalytic properties of NH₂-UiO-66(Zr) and Bi-NPs, results in sensors that possess both high sensitivity and high anti-interference capabilities.

[0049] This invention relates to the fabrication of an As(III) and Cd(II) dual-template ion-imprinted electrochemical sensor. Factors influencing the performance of the molecularly imprinted sensor, such as the type of polymerizable monomer, sensor selectivity, and the ratio of functional monomers to template molecules, were investigated, and optimal fabrication conditions were determined. A glassy carbon electrode (GCE) modified with an AsCd-MIM / NH2-UiO-66(Zr)@Bi ion-imprinted composite film was used for the detection of As(III) and Cd(II) in natural water bodies, exhibiting high sensitivity and specificity. It also features low cost, ease of miniaturization, automation, and a simple fabrication process. Compared to existing methods such as ICP-MS, AAS, electrochemical methods, colorimetric methods, and kit-based methods, the AsCd-MIM / NH2-UiO-66(Zr)@Bi / GCE sensor of this invention can be directly used for the detection of As(III) and Cd(II). The detection process for As(III) and Cd(II) does not rely on large instruments, has a short detection time, is simple to operate, and provides accurate and reliable results.

[0050] Overview of the Invention

[0051] An electrochemical detection method for As(III) and Cd(II) dual-template ion-imprinted electrochemical sensors in water is described, with the following specific steps:

[0052] (1) Using a glassy carbon electrode (GCE) modified with an ion-imprinted composite membrane (AsCd-IIM / NH2-UiO-66(Zr)@Bi) as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum column electrode as the counter electrode, the differential pulse anodic stripping voltammetry (DPASV) was used to measure buffer solutions B with different As(III) and Cd(II) concentrations. Differential pulse voltammetry curves of As(III) and Cd(II) were plotted, and standard curves of As(III) and Cd(II) were obtained by plotting the relationship between peak current and As(III) and Cd(II) concentrations.

[0053] Step (1) Buffer solution B is phosphate buffer solution PBS, with a concentration of 0.1 mol / L and a pH of 5-10. The concentration of As(III) in buffer solution B is 1.0 × 10⁻⁶. -10 ~ 5.0×10 -5 mol L -1 The Cd(II) concentration was 1.0 × 10⁻⁶. -10 ~ 5.0×10 -5 mol L -1 ;

[0054] The differential pulse anodic stripping voltammetry method has an initial potential of -1.2V, an end potential of 1.0V, a pulse amplitude of 0.05s, a pulse period of 0.5s, an amplitude of 0.05V, and an enrichment time of 50~300s.

[0055] The specific steps for preparing the ion-imprinted composite film modified glassy carbon electrode are as follows:

[0056] 1) Pretreatment of glassy carbon electrode: The polished glassy carbon electrode was placed in buffer solution A and cyclic voltammetry was performed until a stable voltammogram was obtained. The polishing method was to place a 6 mm diameter glassy carbon electrode (GCE) on a chamois polishing cloth and polish it with alumina (Al2O3) powder with a particle size of 0.5, 0.3, and 0.05 μm, respectively. Then, it was ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water for 2 min in sequence, and then purged with nitrogen and dried. The pH value of buffer solution A was 6, and buffer solution A contained 0.1 mol / L potassium chloride and 5 mmol / L K3[Fe(CN)6] / K4[Fe(CN)6]. The voltage range of cyclic voltammetry was -0.2~0.6V, the scan rate was 20~120 mV / s, and the equilibrium time was 10 s.

[0057] 2) The pretreated glassy carbon electrode is placed in a sulfuric acid solution and activated by cyclic voltammetry under stirring until a stable voltammogram is obtained. The glassy carbon electrode is then removed, washed with ultrapure water, and dried with nitrogen to obtain the activated glassy carbon electrode. The concentration of the sulfuric acid solution is 0.05~0.5mol / L, the voltage range of the cyclic voltammetry is -0.3~1.3V, and the scan rate is 50~100mV / s.

[0058] 3) A suspension of NH2-UiO-66(Zr) was dropped onto an activated glassy carbon electrode in two portions of 2-5.0 μL each time, and allowed to air dry to obtain an NH2-UiO-66(Zr) / GCE electrode. The suspension was obtained by ultrasonically mixing 1-5 mg of NH2-UiO-66(Zr) with 1 mL of ethanol for 2-4 h. NH2-UiO-66(Zr) was prepared by the following method:

[0059] 0.1–1.0 mmol of ZrCl₄ and 0.1–1.0 mmol of NH₂-BDC were dissolved in 10–30 mL of DMF. After thorough mixing, 0.5–3.0 mL of acetic acid was added and the mixture was sonicated for 15 minutes. The mixture was then transferred to a 50 mL autoclave and reacted at 120°C for 12–24 h. After cooling to room temperature, the mixture was washed three times with DMF to remove unreacted raw materials and impurities, and further washed with ethanol to improve purity. Finally, the product was collected by centrifugation and dried under vacuum for 24 h (120°C) to obtain NH₂-UiO-66(Zr) / GCE.

[0060] 4) Immerse NH2-UiO-66(Zr) / GCE in PBS (0.1-0.5M) electrolyte solution containing 0.1-1.0 mM Bi(NO3)3·5H2O. Under magnetic stirring, uniform sodium bismuth nanoparticles are deposited at a constant potential of -0.9-1.2 V for 70-300 s using a potentiostatic method. The nanoparticles are then gently washed with pure water and air-dried to obtain the NH2-UiO-66(Zr)@Bi / GCE modified electrode.

[0061] 5) An As(III) and Cd(II) imprinted polymer solution was drop-coated onto the surface of an NH2-UiO-66(Zr)@Bi / GCE electrode. A coverslip was then quickly placed over the electrode to aid film formation. The electrode was then subjected to photopolymerization at 15–30 cm under infrared light for 180 min. After the reaction, the electrode was allowed to cool naturally to room temperature. It was then suspended overnight at 2–5 cm in ultrapure water. Once the coverslip was removed, an AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE electrode was obtained. The modified electrode was then eluent with a mixture of EDTA (ethylenediaminetetraacetic acid) and HCl to remove As(III) and Cd(II), yielding an electrochemical sensor with an arsenic and cadmium dual-template imprinted polymer film, designated as the AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE electrode. The wavelength of the red light used was 700–1000 nm. The eluent consists of 0.01 ~ 0.05 M EDTA (ethylenediaminetetraacetic acid) and 0.1 ~ 0.5 M HCl in a volume ratio of 1:1.

[0062] (2) The glassy carbon electrode, reference electrode and counter electrode modified with ion-imprinted composite membrane are placed in a measuring cell containing the sample solution of heavy metals As(III) and Cd(II) to be tested. The sample solution of heavy metals As(III) and Cd(II) to be tested is measured by differential pulse anodic stripping voltammetry under the same conditions as in step (1). The differential pulse curve is plotted to obtain the peak current of As(III) and Cd(II). The peak current of As(III) and Cd(II) is substituted into the standard curve corresponding to step (1) to obtain the concentration of heavy metals As(III) and Cd(II) in the sample solution of heavy metals As(III) and Cd(II) to be tested.

[0063] In this invention,

[0064] Table 1 shows the interaction energy, dipole moment, and number of hydrogen bonds formed at different binding sites of the [AsCd + nMAAPAR] complex in Example 1.

[0065] Table 2 shows the results of As(Ⅲ) and Cd(Ⅱ) determination in actual water bodies using the AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE modified electrode in Example 6 (n=3).

[0066] Example 1: Preparation method of AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE, the specific steps are as follows:

[0067] Materials prepared: ZrCl4 (zirconium source), 2-aminoterephthalic acid (NH2-BDC), N,N-dimethylformamide (DMF), glacial acetic acid, glassy carbon electrode (GCE, 6 mm diameter), alumina powder (0.05 μm, 0.3 μm, 0.5 μm), Nafion (5%, w / v), ethanol, sodium arsenite (NaAsO2), cadmium acetate dihydrate, 2-(2-pyridinium azo)resorcinol (PAR), Bi(NO3)3·5H2O, methacrylic acid (MAA), ethylene glycol dimethacrylate (EDMA), azobisisobutyronitrile (AIBN), HPLC grade acetonitrile (ACN), potassium ferricyanide (K3FeC6N6), hydrochloric acid, ethylenediaminetetraacetic acid (EDTA), disodium hydrogen phosphate, potassium dihydrogen phosphate (purchased from [source]), ultrapure water (18.25 MΩ·cm, 25℃).

[0068] 1) Synthesis of NH2-UiO-66(Zr)

[0069] Under continuous stirring, 0.5 mmol of ZrCl4 and 0.5 mmol of NH2-BDC were dissolved in 20 mL of DMF. After thorough mixing, 1.5 mL of acetic acid was added and the mixture was sonicated for 15 minutes. The mixture was then transferred to a 50 mL autoclave and reacted at 120°C for 24 h. After cooling to room temperature, the mixture was washed three times with DMF to remove unreacted raw materials and impurities, and further washed with ethanol to improve purity. Finally, the product was collected by centrifugation and dried under vacuum for 24 h (120°C) to obtain NH2-UiO-66(Zr).

[0070] 2) GCE surface pretreatment

[0071] A 6 mm diameter glassy carbon electrode (GCE) was placed on a chamois polishing cloth and polished with alumina (Al₂O₃) powders of 0.5, 0.3, and 0.05 μm, respectively. It was then ultrasonically cleaned sequentially with ultrapure water, anhydrous ethanol, and ultrapure water for 2 min each. After purging with nitrogen and drying, it was subjected to a 0.05 mol·L⁻¹ atmosphere. -1 CV activation was performed in H2SO4 (-0.3~1.3V, 100 mV·s). -1 (Scan multiple times until stable). Finally, place in a pH 6.0 buffer solution containing 0.1 mol / L potassium chloride and 5 mmol / L K3[Fe(CN)6] / K4[Fe(CN)6] to determine the degree of activation (voltage range: -0.2 to 0.6 V, scan rate: 20 to 120 mV / s, equilibration time: 10 s).

[0072] 3) Modification of NH2-UiO-66(Zr)

[0073] A suspension of NH2-UiO-66(Zr) was dropped onto an activated glassy carbon electrode and allowed to air dry to obtain an NH2-UiO-66(Zr) / GCE electrode. The suspension was prepared by ultrasonically dispersing 1.0 mg of NH2-UiO-66(Zr) powder in 1.0 mL of ethanol-water (1:1, v / v) containing 0.5% Nafion for 1 h. The amount of NH2-UiO-66(Zr) nanocomposite suspension used was 5~15 μL. Experiments showed that when the amount of NH2-UiO-66(Zr) suspension was greater than 5 μL, the peak current increased with the increase of the amount. However, after exceeding 10 μL, the peak current did not increase significantly with the increase of the amount due to the limited electrode area. Therefore, the optimal amount was selected as 10 μL.

[0074] 4) Electrodeposition of Bi nanoparticles

[0075] Weigh out an appropriate amount of Bi(NO3)3·5H2O, and use 0.1 mol·L... -1 Prepare PBS buffer to a concentration of 0.5 mmol·L⁻¹.-1 A bismuth ion solution was prepared by ultrasonic dissolution and then filtered for later use. The NH₂-UiO-66(Zr) / GCE modified electrode was immersed in the above Bi electrolyte and placed in a three-electrode system (the system consisted of modified GCE as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode). Electrodeposition was performed for 170 s under magnetic stirring at a constant potential of –1.0 V. After electrodeposition, the electrode was removed, gently rinsed with ultrapure water, and allowed to air dry at room temperature to obtain an NH₂-UiO-66(Zr)@Bi / GCE modified electrode with uniformly distributed bismuth nanoparticles on its surface. The deposition of Bi nanoparticles (Bi-NPs) helps improve the electrochemical activity and electron transport rate of the electrode, further enhancing the electrocatalytic response to As(III) and Cd(II).

[0076] 5) Construction of AsCd-IIM imprinted polymeric membrane and template ion elution

[0077] An As(III) and Cd(II) imprinted polymerization solution was drop-coated onto the surface of an NH2-UiO-66(Zr)@Bi / GCE electrode, and then a coverslip was quickly placed on top to assist film formation. Photopolymerization was then carried out under infrared light. After the reaction, the electrode was allowed to cool naturally to room temperature, and then suspended at 4 cm below ultrapure water overnight. After the coverslip detached, the electrode was subjected to 0.05 mol·L⁻¹ water treatment. -1 EDTA + 0.1 mol·L -1 The As(III) and Cd(II) ions were removed by elution in a mixed solution of HCl (volume ratio of 1:1), and then washed with ultrapure water to obtain the AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE modified electrode, which was stored in the refrigerator's crisper drawer. The solvent of the As(III) and Cd(II) imprinted polymerization solution was acetonitrile, and the As(III) and Cd(II) imprinted polymerization solution contained 0.025 mmol / L NaAsO2 (of which NaAsO2 was first dissolved in 100 μL of ultrapure water), 0.05 mmol / L cadmium acetate dihydrate, 0.075 mmol / L 4-(2-pyridinium azo)resorcinol, 0.075 mol / L α-methacrylic acid, 1 mol / L ethylene glycol dimethacrylate, and 0.16 mmol / L azobisisobutyronitrile.

[0078] The crystal structures of NH2-UiO-66(Zr) and NH2-UiO-66(Zr)@Bi were confirmed by X-ray diffraction (XRD) pattern analysis. Figure 1The x1 in the image shows a characteristic diffraction peak at 2θ = 7.2° for NH2-UiO-66(Zr) (1 1 0). The XRD pattern of Bi nanoparticles shows high reflection peaks corresponding to the hexagonal crystal system (rhombohedral phase, JCPDS No. 44-1246), appearing at 26.5° and 28.6°, assigned to the (012) and (104) crystal planes of Bi-NPs, respectively. The results confirm the successful synthesis of NH2-UiO-66(Zr) and NH2-UiO-66(Zr)@Bi. Figure 1 Figure 1a shows the As and Cd imprinted films on NH2-Zr-MOF@Bi before (x2) and after (x3) elution. Due to the polymerization of the imprinted material, the diffraction peaks of NH2-UiO-66(Zr) are masked. This is because the material is encapsulated and covered by the amorphous AsCd-IIM film. After elution, some diffraction peaks appear due to the thinning of the film surface, indicating successful extraction. XRD patterns before and after elution, as well as those obtained with NIP, were also recorded (x4), with the main peak positions remaining consistent across all spectra. Further characterization of the morphology of the prepared NH2-UiO-66(Zr) and NH2-UiO-66(Zr)@Bi was performed using SEM (Figure 1b and 1c). Figure 1 c). This study revealed that NH2-UiO-66(Zr) with an average particle size of 40 × 60 nm exhibits an octahedral structure, while small cubic Bi-NPs are uniformly distributed among the NH2-UiO-66(Zr) nanoparticles. The high surface-to-volume ratio of NH2-UiO-66(Zr) and the uniformly decorated Bi-NPs ensure good conductivity within the network. Figure 1 d shows an imprinted film of As and Cd polymerized on NH2-UiO-66(Zr)@Bi. Figure 1 e shows SEM images of the imprinted membrane after As and Cd removal. As can be seen, after imprinting and polymerization, the material is encapsulated and covered by a highly cross-linked membrane layer, forming a rigid and stable structure. After elution, the membrane surface becomes smoother, with less irregularity and reduced contamination from fixed ions.

[0079] In addition, the surface functional groups of the prepared materials (i.e., AsCd-IIM and AsCd-IIM / NH2-UiO-66(Zr)@Bi) were analyzed by FTIR to verify the success of the synthesis and elution process. Figure 1 f). In the FTIR spectrum of NH2-UiO-66(Zr)@Bi ( Figure 1 F4), the main characteristic peak observed is located at 3233 cm⁻¹. -1 This is attributed to the tensile vibration mode of —NH2. Approximately 640 / 691 cm. -1The peaks are attributed to characteristic peaks of the Zr-O vibration and aromatic C–H out-of-plane bending vibrations, which confirm the successful synthesis of NH2-UiO-66(Zr)@Bi. After imprinting with PAR and MAA ( Figure 1 F1), the main characteristic peak observed is located at 1700 cm⁻¹. -1 and 1628 cm -1 These are attributed to the C=O stretching vibration peak in MAA and the N=N stretching vibration in PAR, respectively. After eluting the template from AsCd-IIM / NH2-UiO-66(Zr)@Bi... Figure 1 F2), resulting in the FTIR spectrum of AsCd-IIM / NH2-UiO-66(Zr)@Bi differing from that before elution ( Figure 1 A significant change occurred compared to F1. At 836 / 954 cm... -1 A small peak nearby can be attributed to the characteristic bending and stretching vibrations of As-O. Two new peaks appeared in the spectrum of AsCd-IIM / NH2-UiO-66(Zr)@Bi compared to the eluted version, located at 1273 / 1328 cm⁻¹. -1 The interaction between the NH2 group and the arsenite ion was confirmed by NO stretching. Additionally, at 539 cm⁻¹... -1 The peaks appearing within the range are due to the stretching vibrations of the Cd-O bond, confirming the interaction between the monomer and cadmium (Cd). 2+ Coordination. These surface-imprinted sites not only provide more sites for the selective adsorption of free electrolyte ions on the electrode surface, but also enhance the ionic conductivity of the electrode-electrolyte interface. (See figure...) Figure 1 Curve F3 is similar to curve F4, which is the infrared scanning contrast curve of NIM / NH2-Zr-MOF@Bi. Additionally, the curves before elution from AsCd-MIM / NH2-UiO-66(Zr)@Bi (…) Figure 1 g) after ( Figure 1 EDX spectral analysis (h) clearly shows that the four main elements C (red), O (blue), Cd (yellow), and As (purple) are uniformly distributed within the AsCd-IIM / NH2-UiO-66(Zr)@Bi network before elution. After repeated washing of the prepared polymer with the eluent, the wt% content of AsCd decreased from 4.59% and 1.51% to 0.01% and 0.05%, respectively. The network distribution of the material is mainly dominated by C (red), ensuring the elution of imprinted sites. Simultaneously, the uniform adsorption active sites left after elution ensure accessibility to the template and consistent electron transfer kinetics on the electrode surface. These factors collectively contribute to improving the sensitivity and reproducibility of the imprinted electrochemical sensor.

[0080] During the AsCd-IIM preparation process, DFT theoretical simulations were used to screen the optimal functional monomers MAA and PAR from nine different functional monomers (MAA, AM, 1-VLD, ATU, MA, PAR, EA, 2-AP, AL). MAAPAR was then selected as the preferred monomer for further optimization of the AsCd monomer ratio from 1:1:1:1 to 1:2:4:4. The optimized geometry is shown below. Figure 2 As shown in the figure, the optimized structure indicates that the combination of AsCd and MAA,PAR has a clear stretch and relatively small steric hindrance at a ratio of 1:2:3:3. From the calculated and statistically analyzed binding energies of AsCd and MAA,PAR at ratios of 1:1:1:1 to 1:2:4:4 (Table 1), the lowest non-covalent binding energy is –846.79 kJ / mol when As:Cd:MAA:PAR = 1:2:3:3. −1 According to the optimized structure, when the amount of MAAPAR is three times that of As2Cd, the two Cd atoms mainly form three-coordinate imprinted sites with O22, O48, and O74 in the three PAR monomers, and four-coordinate traps with N6 / 13 / 32 / 39 in the two isomer PARs, with average bond lengths and bond angles of 2.11 Å, 2.32 Å and 141.54°, 117.88°, respectively. For arsenic, in addition to forming a 2.44 Å coordination with N58 in PAR, O97 / 109 and H88 in MAA form strong hydrogen bonds with H82 / 83 and O80 in H3AsO3, with average bond lengths and bond angles of 1.46 Å and 142.37°. Further increasing the amount of MAAPAR monomers not only introduces inter-monomer hydrogen bonds but also increases steric hindrance, leading to a reduction in effective hydrogen bonds. Furthermore, the higher dipole moment and polarizability enhance hydrogen bonding and non-covalent interactions, making IIP more selective for polar analytes. Therefore, a stoichiometric ratio of 1:2:3:3 was selected as the optimal molar ratio.

[0081] Example 2: Electrochemical performance of AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE

[0082] To confirm the electrochemical performance of different modified electrodes, characterization was performed using CV and EIS. The electrode contained 5.0 mM [Fe(CN)6] 3- / 4 Characterization was performed in 0.1 M KCl solution at a scan rate of 100 mV / s in the range of -0.2 V to 0.6 V. Figure 3As shown in Figure A, compared to bare GCE (a), when GCE is modified with NH2-UiO-66(Zr)@Bi, the redox peak area and response current increase (b), which is attributed to the large specific surface area and enhanced conductivity of NH2-UiO-66(Zr) and Bi-NPs. When a dense AsCd-IIM film is formed on the surface of the composite material via infrared polymerization, the weakly conductive imprinted film layer makes [Fe(CN)6]... 3- / 4 The electron transport rate is hindered, leading to a significant decrease in the conductivity of the modified electrode. When the template AsCd is eluted from the AsCd-IIM film (d), the partially imprinted cavity formed allows [Fe(CN)6] to... 3- / 4- Probe electrons can easily pass through these cavities to reach the material surface for electron transfer. Therefore, the eluted ion-imprinted polymer film causes the redox peak to reappear. EIS measured under the same conditions is as follows: Figure 3 As shown in B. Charge transfer resistor (R CT The diameter of the semicircle is represented by ). The order of the diameters of the different semicircles is AsCd-IIM / NH2-UiO-66(Zr)@Bi > IIM / NH2-UiO-66(Zr)@Bi > GCE > NH2-UiO-66(Zr)@Bi. This phenomenon is mainly attributed to the synergistic enhancement of the electrochemical performance of the NH2-Zr-MOF@Bi composite by NH2-UiO-66(Zr) and Bi. The semicircle diameter increases after a dense thin film is polymerized. This blocking effect is based on the insulating properties of the uneluted IIM film. After elution, the departure of template ions creates imprinted pores in the IIM, reducing its electron transfer impedance, but still higher than that of bare GCE, consistent with CV results.

[0083] Example 3: Selectivity, repeatability and stability of AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE

[0084] In analytical applications, the size and functional groups of coexisting ions, molecules, or structural analogs must be considered. To test the selectivity of AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE for AsCd, a concentration higher than the target analyte (0.3 μmol / L) was added to the analytical sample. -1 To investigate the sensor's anti-interference capability, an interference agent at a concentration 50 times that of AsCd was used. Figure 4As shown, with the addition of interfering substances (MgCl2, CuSO4, CaCl2, KCl, NaCl, ascorbic acid, and glucose), the sensor's response to the interfering substances is only slightly higher than the background current. When template analytes are added again while the interfering substances are present, the sensor's current response to As and Cd is much greater than that to other interfering analytes. NIP, however, is insensitive to AsCd, with its current only slightly higher than the background current. This indicates that the amount of AsCd bound to the imprinted film is much greater than the binding amount of other interfering ions / molecules. This higher current response on the imprinted electrode is attributed to the specific interaction between the imprinted film layer (AsCd-MIM) on the sensing electrode surface and the template ions.

[0085] To evaluate the reproducibility of the electrochemical sensor, ten AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE sensing electrodes were prepared under the same conditions. The diffusive current (DPV) response was measured in PBS with 5 μM AsCd. The RSDs for AsCd were as low as 3.2% and 4.2%, respectively, indicating good reproducibility of the sensor. Simultaneously, each electrode underwent up to 10 consecutive elution and reabsorption tests, and the calculated RSDs for the DPV corresponding intensities of As and Cd were 2.8% and 3.9%, respectively, indicating good stability of the sensor. Similarly, to evaluate the storage stability of the sensor, the prepared AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE electrodes were stored in a refrigerator at room temperature for 4 weeks. The peak current intensities of As and Cd were 95.5% and 95.7% of the initial current response, respectively. These evaluations demonstrate the good stability, excellent reproducibility, and repeatability of AsCd-MIM / NH2-Zr-MOF@Bi / GCE.

[0086] Example 4: Electrochemical detection method for AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE, specifically as follows:

[0087] Using the glassy carbon electrode (GCE) modified with the ion-imprinted composite film prepared in Example 1 as the working electrode, the Ag / AgCl electrode as the reference electrode, and the platinum column electrode as the counter electrode, the buffer solutions B with different As(III) and Cd(II) concentrations were measured by differential pulse anodic stripping voltammetry (DPASV). AsCd differential pulse voltammetry curves were plotted, and the AsCd standard curve was obtained by plotting the relationship between peak current and As(III) and Cd(II) concentrations. The glassy carbon electrode modified with the ion-imprinted composite film was an AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE modified electrode.

[0088] The buffer solution B is phosphate buffer solution (PBS), with a concentration of 0.1 mol / L and a pH of 6. The As(III) concentration in buffer solution B is 1.0 × 10⁻⁶. -10 ~ 5.0×10 -5 mol L -1 The Cd(II) concentration was 1.0 × 10⁻⁶. -10 ~ 5.0×10 -5 mol L -1 ;

[0089] The differential pulse anodic stripping voltammetry method has an initial potential of -1.2V, an end potential of 1.0V, a pulse amplitude of 0.05s, a pulse period of 0.5s, an amplitude of 0.05V, and an enrichment time of 50~300s.

[0090] The differential pulse voltammetry standard curves for As(Ⅲ) and Cd(Ⅱ) in this embodiment are shown in [reference needed]. Figure 5 A. Differential pulse voltammetry (DPV) tests showed that Cd(II) and As(III) exhibited distinct oxidation peaks at -0.85 V and +0.78 V, respectively, on the sensor surface. The peak positions were well separated, indicating feasibility for simultaneous detection. As the AsCd concentration in the mixed solution increased to 2.0 × 10⁻⁶, the... -10 ~3.2 ×10 -5 mol L -1 As the concentration increases within the specified range, the peak current responses of both metal ions increase synchronously and show a good linear relationship with the logarithm of concentration. Specifically, the response curve of Cd(II) exhibits bilinear characteristics in different concentration ranges: in the low concentration range (<2 μmol·L⁻¹), the peak current responses of both metal ions increase synchronously and show a good linear relationship with the logarithm of concentration. -1 The fitted equation is I(μA) = 2.12 + 0.40logC Cd (μmol L) -1 (R) 2 = 0.986), high concentration range (>2μmol·L -1 The expression is I(μA) = 2.93 + 1.74logC. Cd (μmol L) -1 (R) 2 = 0.999) Figure 5 C); As(Ⅲ) exhibits a single linear relationship throughout the entire test range, with the fitted equation being I(μA) = 1.74 + 0.38logC As (μmol L) -1 (R) 2 =0.998)( Figure 5(D) The detection limit (LOD, S / N = 3) of AsCd, calculated according to the 3σ / S principle, is 0.13 nM, demonstrating extremely high detection sensitivity. This superior performance is mainly attributed to the enhancement of the electrochemical activity of As(III) by the Bi nanofilm, the enrichment capacity of metal ions by the high specific surface area and porous structure of NH2-Zr-MOF, and the specific recognition characteristics imparted by the ion-imprinted membrane. The constructed sensor exhibits excellent comprehensive performance in terms of resolution, sensitivity, and response stability, possessing the potential for simultaneous detection of trace heavy metal ions in complex water samples.

[0091] Example 5: Actual sample analysis of AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE, specifically:

[0092] The AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE, reference electrode, and counter electrode were placed in the measuring cell of the actual sample solution to be tested. The sample solution was measured using differential pulse anodic stripping voltammetry under the same conditions as in step (1). The differential pulse curve was plotted to obtain the peak currents of As(III) and Cd(II). The peak currents of As(III) and Cd(II) were substituted into the corresponding standard curve in Example 4 to obtain the concentrations of heavy metals As(III) and Cd(II) in the actual sample solution.

[0093] The sample preparation method was as follows: After simple centrifugation of the actual water body, the supernatant was collected and filtered through a 0.22 μM membrane filter, then uniformly mixed with 0.1 M PBS (pH 6.0) to obtain the analytical sample. For spiked samples, As(III) and Cd(II) stock solutions were added to the real sample using the standard addition method for determination. The results are shown in Table 2. It can be seen that after three parallel determinations, the average detection values ​​of As and Cd in Yangzonghai and Panlongjiang waters were less than 0.22 nmol / L. -1 0.45 nmol L -1 and 0.76 nmol L -1 0.46 nmol L -1 All were less than 5 μg / L -1 and 0.015 mg L -1 The method conforms to the standards of the World Health Organization and national standards. The relative standard deviation (RSD) of AsCd determined by the standard addition method was less than 4.5%, and the recovery rate ranged from 98% to 110%, indicating that the method has good accuracy and reliability.

[0094]

[0095]

[0096] The specific embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. An As(III) and Cd(II) ion-imprinted electrochemical sensor, characterized in that: Includes a substrate electrode and a surface ion-imprinted composite sensing film coated on the surface of the substrate electrode; The composite sensing membrane consists of three layers from bottom to top, including: (1) Amino-functionalized zirconium-based metal-organic framework material NH2-UiO-66(Zr) layer; (2) Bismuth nanoparticles (Bi-NPs) layer attached to the amino-functionalized zirconium-based metal-organic framework material NH2-UiO-66(Zr) layer; (3) As(Ⅲ) and Cd(Ⅱ) ion-imprinted polymer films formed by infrared-initiated polymerization.

2. The As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 1, characterized in that: The substrate electrode is a pretreated glassy carbon electrode (GCE) with a diameter of 3 to 6 mm. The pretreatment includes: polishing the glassy carbon electrode sequentially with alumina powder with particle sizes of 0.5 μm, 0.3 μm, and 0.05 μm; then ultrasonically cleaning it sequentially with pure water, ethanol, and pure water for 2-5 min, and air-drying it naturally; then placing the electrode in a sulfuric acid solution with a concentration range of 0.1-1.0 mol / L, and performing 5-20 cyclic voltammetry scans at -0.3-1.3 V under stirring conditions, with a scan rate of 20-100 mV / s to activate the electrode; then placing it in a buffer solution containing 0.1 mol / L potassium chloride and 5 mmol / L K3[Fe(CN)6] / K4[Fe(CN)6] (pH 6.0) for cyclic voltammetry scans until a stable cyclic voltammogram is observed, and then washing it with ultrapure water; and finally air-drying it for later use.

3. The As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 2, characterized in that: An amino-functionalized zirconium-based metal-organic framework material NH2-UiO-66(Zr) layer is deposited on a pretreated glassy carbon electrode, including the following schemes: Dissolve 0.1–1.0 mmol of ZrCl4 and 0.1–1.0 mmol of NH2-BDC in 10–30 mL of DMF; after mixing thoroughly, add 0.5–3.0 mL of acetic acid and sonicate for 10–20 minutes; then transfer the mixture to a 50–100 mL high-pressure reactor and react at 115–125 °C, preferably 120 °C, for 12–24 h; after cooling, wash at least twice with DMF to remove unreacted raw materials and impurities, then wash with ethanol, and finally centrifuge to collect the centrifuged product. The centrifuged product is then vacuum dried at 115–125 °C for 20–28 h to obtain NH2-UiO-66(Zr); 0.5–5.0 mg of NH2-UiO-66(Zr) was dispersed in 1.0–5.0 mL of ethanol and sonicated for 8–15 min to obtain a uniform and stable suspension. Subsequently, 2–5.0 μL of the suspension was dropped onto the surface of the pretreated glassy carbon electrode in two separate drops to obtain NH2-UiO-66(Zr) / GCE.

4. The As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 3, characterized in that: A bismuth nanoparticle layer was arranged on NH2-UiO-66(Zr) / GCE, including the following methods: Immerse NH2-UiO-66(Zr) / GCE in a solution containing 0.1 ~ 1.0 mM Bi 3+ In a PBS electrolyte solution; under stirring conditions, uniform sodium bismuth nanoparticles were deposited at a constant potential of -0.9 ~ -1.2 V for 70 ~ 300 s using a potentiostatic method. Then, the particles were gently washed with pure water and dried to obtain an NH2-UiO-66(Zr)@Bi / GCE modified electrode; the PBS electrolyte solution was 0.1 ~ 0.5 M PBS electrolyte solution.

5. The As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 4, characterized in that: As(III) and Cd(II) ion-imprinted polymer films formed by infrared-initiated polymerization on NH2-UiO-66(Zr)@Bi / GCE modified electrodes include the following schemes: The template-functional monomer polymerization solution was dissolved in 300-500 μL of acetonitrile. Then, 10.0-50.0 μL of the polymerization solution was added dropwise to the surface of the NH2-UiO-66(Zr)@Bi / GCE modified electrode. After covering with a glass slide, the polymerization was carried out under infrared lamp irradiation for 2-6 hours. Then, the template ions As(Ⅲ) and Cd(Ⅱ) were removed by elution solution to obtain AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE.

6. The As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 5, characterized in that: The template-functional monomer polymerization liquid is configured through the following steps: Sodium arsenite, cadmium acetate dihydrate, and functional monomers MAA and 4-(2-pyridinium azo)resorcinol (PAR) were dissolved in 300-800 μL of acetonitrile at a molar ratio of 1:1:1:1 to 1:2:4:

4. After sonication for 8-15 min, the mixture was allowed to stand to allow the template and monomers to react fully. Then, 0.1-1.0 mmol of ethylene glycol dimethacrylate was added, and sonication was continued for 3-10 min. Afterward, 0.01-0.08 mmol of azobisisobutyronitrile was added, and the mixture was sonicated for 5-15 min before being stored in a refrigerator. Before adding NaAsO2 to acetonitrile, the prepared NaAsO2 was first dissolved in 50-100 μL of ultrapure water. After dissolving in acetonitrile, the concentration of sodium arsenite was 0.0125-0.05 mmol / L (please consider whether the data highlighted in yellow is reasonable), preferably 0.025 mmol / L.

7. The As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 5, characterized in that: The elution solution consists of 0.01-0.05 M EDTA (ethylenediaminetetraacetic acid) and 0.1-0.5 M HCl, with a volume ratio of 1-2:1-2.

8. An electrochemical detection method for an As(III) and Cd(II) ion-imprinted electrochemical sensor as described in any one of claims 1-7, characterized in that: Using an As(III) and Cd(II) ion-imprinted electrochemical sensor as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum column electrode as the counter electrode, differential pulse anodic stripping voltammetry (DPASV) was used to measure buffer solutions B with different As(III) and Cd(II) concentrations. Differential pulse curves of As(III) and Cd(II) were plotted, and standard curves of As(III) and Cd(II) were obtained by plotting the relationship between peak current and As(III) and Cd(II) concentrations. The As(III) and Cd(II) ion-imprinted electrochemical sensor was an AsCd-IIM / NH2-UiO-66(Zr)@Bi / GCE modified electrode.

9. The electrochemical detection method of an As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 8, characterized in that: Buffer solution B is phosphate-buffered saline (PBS), with a concentration of 0.1–0.5 mol / L, containing 0.1–0.5 mol / L KCl, and a pH of 5–10. The concentrations of As(III) and Cd(II) in buffer solution B are 1.0 × 10⁻⁶. -10 ~5.0 ×10 -5 mol / L; The solution includes an aqueous solution.

10. The electrochemical detection method of an As(III) and Cd(II) ion-imprinted electrochemical sensor according to claim 8, characterized in that: The DPASV voltammetric method has an initial potential of -1.2V, an end potential of 1.0V, a pulse amplitude of 0.01 ~ 0.05s, a pulse period of 0.1 ~ 0.5s, an amplitude of 0.01 ~ 0.05V, and an enrichment time of 50 ~ 300s.